Interactive effects of added L-carnitine and chromium picolinate on sow reproductive performance - Real, D.E.; Owen, K.Q.; Stoller, S.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 599 sows were used to determine the effects of added L-carnitine and/or chromium picolinate on reproductive performance. Experimental treatments were arranged in a 2 × 2 factorial with main effects of added L-carnitine (0 or 50 ppm) and chromium picolinate (0 or 200 ppb). Starting on the first day of breeding, sows were provided a daily top dress containing the carnitine and(or) chromium along with the standard gestation diet. Dietary treatments were administered daily through the initial gestation, lactation, and through a second gestation period (2 parities). During the first parity, there was a carnitine × chromium interaction (P<0.01) for first service farrowing rate. Added dietary chromium increased (P<0.01) first service farrowing rate, but not when carnitine was added. No differences (P>0.05) were observed in number of pigs born alive, still born, mummies, or total born in the first parity. Added dietary L-carnitine decreased (P<0.05) wean to estrus interval, and tended to increase (P<0.08) the number of sows in estrus by d 7. In the second parity, a tendency (P<.08) for a carnitine × chromium interaction was found for first service farrowing rate. Adding carnitine and chromium together in the diet increased first service farrowing rate compared to either product alone. Because of the change in wean-to-estrus interval and farrowing rate, feeding additional dietary carnitine and chromium increased (P<0.04) the percentage of sows that were weaned from parity 1 and farrowed in parity 2. When calculating the total number of pigs and number born alive based on all sows that were started on test, both added carnitine and chromium increased the number of pigs born and born alive. These results show that carnitine and chromium supplementation improved return-to- estrus interval and farrowing rate and, thus, total number born alive over two parities.
Keywords: Swine; Sows; L-carnitine; Chromium Picolinate